The EUPEMEN (EUropean PErioperative MEdical Networking) Protocol for Acute Appendicitis: Recommendations for Perioperative Care - Ioannidis, Orestis; Anestiadou, Elissavet; Ramirez, Jose M; Fabbri, Nicolò; Ubieto, Javier Martínez; Feo, Carlo Vittorio; Pesce, Antonio; Rosetzka, Kristyna; Arroyo, Antonio; Kocián, Petr; Sánchez-Guillén, Luis; Bellosta, Ana Pascual; et al. (Journal of clinical medicine, 2024)
Background/Objectives: Acute appendicitis (AA) is one of the most common causes of emergency department visits due to acute abdominal pain, with a lifetime risk of 7-8%. Managing AA presents significant challenges, particularly among vulnerable patient groups, due to its association with substantial morbidity and mortality. Methods: The EUPEMEN (European PErioperative MEdical Networking) project aims to optimize perioperative care for AA by developing multidisciplinary guidelines that integrate theoretical knowledge and clinical expertise from five European countries. This study presents the key elements of the EUPEMEN protocol, which focuses on reducing surgical stress, optimizing perioperative care, and enhancing postoperative recovery. Results: Through this standardized approach, the protocol aims to lower postoperative morbidity and mortality, shorten hospital stays, and improve overall patient outcomes. The recommendations are tailored to address the variability in clinical practice across Europe and are designed to be widely implementable in diverse healthcare settings. Conclusions: The conclusions drawn from this study highlight the potential for the EUPEMEN protocol to significantly improve perioperative care standards for AA, demonstrating its value as a practical, adaptable tool for clinicians.
Keywords: laparoscopic appendectomy; perioperative care; training and dissemination; appendectomy; appendicitis diagnosis score; acute appendicitis; enhanced recovery after surgery; surgical rehabilitation; appendicitis guidelines; EUPEMEN project